Multiple gene loci for a single species of glycine transfer ribonucleic acid. - Fleck, E W (1975)
The study of suppressors of tryptophan synthase A protein missense mutations in Escherichia coli has led to the establishment of two nonadjacent genetic loci (gly V and gly W) specifying identical nucleotide sequences for a single isoaccepting species of glycine transfer ribonucleic acid (tRNA GLY 3 GGU/C). In one case, suppression of the missense mutation trpA78 was due to a mutation in a structural gene (gly W) for tRNA Gly 3 GGU/C. This mutation resulted in a base change in the anticodon and modification of an A residue adjacent to the 3' side of the anticodon, leading to the production of a tRNA Gly 3 UGU/C species. The resulting glyW51 (SU UGU/C) allele was mapped by interrupted mating and was located at approximately 37 min on the Escherichia coli genetic map. Other suppressor mutations affecting the primary sequence of tRNA Gly GGU/C and giving rise to the Ins and SU+A58 phenotypes were positioned at 86 min (glyV). Several independently arising missense suppressor mutations resulting in the SU+A78 phenotypes were isolated and mapped at these two genetic loci (glyV and glyW). The ratio of appearance of suppressor mutations at glyV and glyW suggests that there are three of four tRNAGly3 GGU/C structural gene copies at the glyV locus to one copy at the glyW locus. Structural genes for tRNA ly isoacceptors are now known at four distinct locations on the Escherichia coli chromosome: glyT (77 MIN), TRNA Gly 2 GGA/G; gly U (55 min), tRNAGly-1 minus; and gly V (86 MIN) AND GLYW (37 min), tRNAGly 3 GGU/C.